Tort Liability Resulted from Negligence in Infectious Diseases under the Iraqi Legal System: Coronavirus (COVID-19) as an Example - Othman, Arez Mohammed Sediq (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Despite the fact that the issue of Coronavirus pandemic is quite new to Iraq and the emergency response of public authorities might be inefficient in many ways, the application of legal rules is vital to prevent further spread of the virus and to provide a legal basis for compensation based on a tort liability of the infected patient toward others. States are undergone difficult circumstances and crises but priority will remain for the rule of law and public well-being should always be prevailed. Given the fact that public authorities are in a state of shock and trial procedures against the infected patient who transmit the disease to other might be challenging or even inadmissible at this stage, the paper argues that in response to the widespread suffering and death that Coronavirus has caused to many, the court should allow the victim to held the person who transmitted the disease responsible with tort liability and be able to seek fair compensation. Further, it would also argue that awareness raising is not the only solution to prevent the spread of the virus, infected patients shall be held responsible as a way to enhance precaution mechanisms. The paper will focus on tort liability of the infected negligent person in case he or she transmit the virus to others and caused physical or moral injuries under the Iraqi legal system.